Another look at inheritance of uniform continuity of 1-dimensional aggregation functions by their super-additive transformations - Fateme Kouchakinejad; Alexandra Siposova (Journal of Mahani Mathematical Research)
In an earlier paper by Seliga, Siran and the second author (J. Mahani Math. Res. Center 8 (2019) 37–51) on lifting continuity properties of aggregation functions to their super- and sub-additive transformations it was shown that uniform continuity is preserved by super-additive transformations in dimension 1. We give a shorter and more direct proof of this result and of a related linear bound on uniformly continuous aggregation functions.